TURP syndrome: à propos d’un cas - Benlamkaddem, Said (Pan Afr Med J, 2017)
We report the case of a 78-year old patient, with no particular past medical history, who underwent transurethral resection of the prostate (50 g) under spinal anesthesia for benign hypertrophy. 90 minutes after the beginning of the procedure, the patient had nausea, vomiting, visual fog and bradycardia, suggesting TURP syndrome. Ionogramme objectified a serum sodium level of 118meq/L, hence the patient was treated with 3% hypertonic saline solution, with good evolution. This study describes a common but moderate occurrence of TURP syndrome whose management was facilitated by patient’s alertness during spinal anesthesia.